Surgical Management of Lower Back Pain: Is Optimizing Spinopelvic Alignment Beneficial for Patient Outcomes? - Dieter Thijs; Ardavan Kashtiara; Sarah Beldé; Erik Van de Kelft (Life)
For the past two decades, the consideration of spinopelvic parameters, sagittal balance, and spine shape has gained importance in the diagnosis and optimal surgical management of painful adult spinal deformity. These principles are used with increasing frequency in the surgical planning and treatment of degenerative mechanical lower back pain. Several parameters exist to analyze both global and regional spinal balance. Chronic lower back pain due to degenerative disc disease, degenerative spondylolisthesis, or adult spinal deformity can be surgically managed in a multitude of ways ranging from simple decompression to multilevel arthrodesis with or without corrective osteotomies, depending on the presumed etiology of the pain, surgical planning, and the surgical goal. In surgical candidates, preoperative evaluation of spinopelvic parameters is paramount, as increasing evidence shows that restoration of the shape of the spine while respecting these parameters improves patient-reported outcome measures (PROMs), decreases re-operation rates, and reduces mechanical complications such as proximal junctional kyphosis/failure (PJK/PJF), distal junctional kyphosis/failure (DJK/DJF), adjacent segment disease (ASD), and rod fracture. This review provides a conceptual analysis of spinopelvic alignment, global and regional sagittal balance, and the restoration of the spine’s shape in relation to patient outcomes during surgical treatment of degenerative spine disorders.